Structured Oral Corrective Feedback in Business English Job Interview Simulations - Zaenul Wafa; Endang Susilowati; Eka Fanti Sulistiyaningsih (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Job interview speaking requires grammatical control, appropriate professional register, organized self-presentation, and confidence under time pressure. This study investigated the implementation and classroom outcomes of structured oral corrective feedback (OCF) in a Business English course. The study conducted from April to June 2026 at Universitas An Nuur, Indonesia, the study involved 61 second semester Management students from two intact classes. A classroom-based explanatory mixed methods design combined a one-group pretest posttest procedure with observation of feedback episodes, an eight-item confidence questionnaire, written reflections, and semi-structured interviews. During six 90-minute meetings, students completed progressively less scripted job interview simulations and received explicit correction, recasts, clarification requests, metalinguistic prompts, and delayed group feedback. The overall speaking mean rose from 63.12 to 78.46, with the largest gain in professional expression. The improvement was statistically significant, t(60) = 12.97, p < .001, Cohen’s dz = 1.66. Of 194 observed feedback episodes, 69.6% produced successful uptake. Explicit correction generated the largest number of successful repairs, whereas delayed feedback was preferred during complete responses because it protected fluency and concentration. Qualitative evidence indicated greater awareness of recurring errors, more appropriate workplace wording, and stronger readiness to speak without full scripts. The findings suggest that structured OCF in Business English should integrate linguistic accuracy with register, relevance, answer organization, and strategic self-presentation.